Characterization of Agarolytic Bacterium Microbulbifer elongatus PORT2 and Its GH16 Agarase - Santi Rukminita Anggraeni; Marion B. Ansorge-Schumacher (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
Sugars from agar exhibit potential biological activities and comprise a sustainable source of third-generation biofuel. Their provision through enzyme-assisted bioconversion of agar is considered a mild and environmentally-friendly process. This work reports a mesophilic-agarolytic bacterium characterization from Batu Karas, West Java-Indonesia coastal seawater. Analysis 16S rRNA showed a phylogeny relationship of the bacterium to the genus Microbulbifer, especially to M. elongatus. A gene coding for agarase AgaF16A was cloned and expressed in E. coli BL21(DE3) using a genome mining approach. The protein sequence of AgaF16A showed 86.79% similarity to the catalytic domain of glycoside hydrolase (GH) 16 b-agarase from Microbulbifer thermotolerans JAMB-A94. The enzyme cleaved agarose and agar oligomers larger than neoagarooctaose into neoagarohexaose and neoagarotetraose. It also showed activity on natural agar extracted from Indonesian agarophytes. The AgaF16A was active in wide pH and temperature ranges. It retained more than 80% activity after one hour incubation at 50 °C, indicating thermostability, favorable for technical application.